2019
DOI: 10.1002/cam4.2045
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic alterations of plasma cell free DNA in response to chemotherapy in children with neuroblastoma

Abstract: Background To improve cure rates for neuroblastoma (NB), it is important and necessary to evaluate therapy response. Our investigation focuses on using plasma cell free DNA (cfDNA) as a biomarker to determine tumor burden and minimal residual disease (MRD) of NB patients during chemotherapy. Methods Total 58 NB patients were recruited from July 2016 to December 2017. Therapy regime and risk classification were based on COG standard and BCH‐NB‐2007 protocol. RECIST study was used to judge response to therapy at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
(69 reference statements)
0
9
0
1
Order By: Relevance
“…cfDNA is thought to originate predominantly from tumor cells and hematopoietic cells [34]. We previously showed that inflammation, transfusion, and therapy with granulocyte-colony stimulating factor are key clinical factors affecting the quantification of cfDNA [35]. To avoid detection of cfDNA from non-tumor cells, blood should not be sampled for tumor cfDNA analysis in these three settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cfDNA is thought to originate predominantly from tumor cells and hematopoietic cells [34]. We previously showed that inflammation, transfusion, and therapy with granulocyte-colony stimulating factor are key clinical factors affecting the quantification of cfDNA [35]. To avoid detection of cfDNA from non-tumor cells, blood should not be sampled for tumor cfDNA analysis in these three settings.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that plasma cfDNA levels correlated strongly with tumor burden in children with NB [23], and could potentially serve as a more effective biomarker than LDH, which is widely used in the clinic. Furthermore, plasma cfDNA concentrations were significantly lower in patients with PR compared with SD, and the concentrations were dynamically associated with changing tumor burden in response to chemotherapy [35]. However, whether cfDNA could serve as an effective molecular marker for recurrence was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in recent years, many reports have confirmed the important role of cfDNA in the diagnosis and prognosis of renal cancer, colorectal cancer, neuroblastoma, and pancreatic cancer. [18][19][20][21] Based on the above research results, cfDNA may be a specific, non-invasive and cost-effective new biomarker, which has great potential value for clinical cancer detection. This study performed a quantitative study on the plasma cfDNA concentration changes in patients with advanced GC chemotherapy during chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…To depict tumor heterogeneity and minimal residual disease, liquid biopsy is recommended to estimate tumor dynamics [24][25][26][27][28]. Recently, plasma cell-free DNA (cfDNA) quantification is emerging as a promising and noninvasive method to predict tumor burden in NB [29][30][31]. More importantly, serum or plasma MYCN copy number quantification by real-time quantitative polymerase chain reaction (qPCR) was used to predict amplified MYCN of tumor in NB, at different cutoff value [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%